1996
DOI: 10.1029/96ja02327
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of gravity wave modulation of midlatitude sporadic E layers

Abstract: We have used a computer simulation to study gravity wave modulation of midlatitude sporadic E (Es) layers. It is shown that a horizontally stratified Es layer may be deformed by gravity waves and become a large‐scale wavelike structure. Spatial resonance is not required for significant modulations to form. For a southward propagating gravity wave the south side sections of the wavelike deformed Es layer may overturn and appear as field‐aligned features stretching about 10 km in altitude. The deformed Es layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 26 publications
(13 reference statements)
5
40
1
Order By: Relevance
“…Yamamoto et al, 1991;Ogawa et al, 1995Ogawa et al, , 2002, which suggests that these fluctuations are invoked by AGWs and/or polarization electric fields in an E s (Huang and Kelley, 1996;Horinouchi et al, 2002;Horinouchi, 2004;Yokoyama et al, 2004bYokoyama et al, , 2005. Strong electric field fluctuations were actually found from the rocket flights during SEEK-1 (Pfaff et al, 1998) and SEEK-2 (Wakabayashi et al, 2005).…”
Section: Introductionmentioning
confidence: 83%
“…Yamamoto et al, 1991;Ogawa et al, 1995Ogawa et al, , 2002, which suggests that these fluctuations are invoked by AGWs and/or polarization electric fields in an E s (Huang and Kelley, 1996;Horinouchi et al, 2002;Horinouchi, 2004;Yokoyama et al, 2004bYokoyama et al, , 2005. Strong electric field fluctuations were actually found from the rocket flights during SEEK-1 (Pfaff et al, 1998) and SEEK-2 (Wakabayashi et al, 2005).…”
Section: Introductionmentioning
confidence: 83%
“…The data presented here support the idea proposed by Woodman et al (1991) of gravity wave modulation of Es-layers, but the large periods observed cannot support a resonance mechanism. In a recent numerical study Huang and Kelley (1996) have shown that spatial resonance is not required to obtain signi®cant modulation of the height of an Es-layer, but their work should be extended to longer-period waves to account for our observations.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Substituting (5) -(9) into (1) -(4), similar to the procedure used in the simulations of gravity wave modulation of midlatitude sporadic E layers [Huang and Kelley, 1996b], we obtain the coupled equations for •p and N and then solve them numerically. We assume that the …”
Section: Model Equationsmentioning
confidence: 99%